Factors Affecting the Utilization of ICT in Teaching and Learning Science Subjects in Senior Secondary Schools Tarauni Local Government Area of Kano State - Nahannu, M.S.; Muzammil, M.; Garba, S.; Haruna, S.S. (International Journal of Scientific Research in Computer Science and Engineering, 2023)
The study used a cross-sectional survey research design. The targeted population of the study comprised all science teachers in senior secondary school within Tarauni local government area of Kano state. Purposive sampling technique was used to select the senior secondary school and simple random sampling technique was employed to select 35 science teachers from these schools. Questionnaire was adapted as research instrument to collect data from the teachers for the purpose of answering research questions. The study used descriptive statistics as a method of data analysis. The study found that the use of Information and Communication Technology in teaching and learning science subjects is affected by numerous factors and these factors greatly impacted science teachers’ and students’ capabilities of using Information and Communication Technology for the teaching-learning process. These factors were found to be teacher-level factors, cost-related factors and technological-related factors.